Improving the Performance of Decking Board for Use in Landscape Design - R. Safin, R.; F. Ilalova, G.; R. Hasanshin, R. (International Journal of Engineering and Technology, 2018)
In recent years improving the efficiency of wood use is gaining ever-increasing relevance both in Russia and abroad. In issues related to the thermal modification of the properties of wood the increased interest of scientific community can be observed. Heat treatment causes a change in the physical properties and chemical composition of wood raw materials, which subsequently contributes to improvement of the performance characteristics of composite materials and the production efficiency of chemical products from thermally modified shredded wood. The purpose of developing this technology is to improve the performance characteristics of products made of wood-polymer compositions, as well as improved final qualities of the material, namely, the absence of the odor characteristic of thermowood and the formation of cracks on the surface of the material. The effect of the preliminary heat treatment of ground wood in disc-type reactors on water absorption, swelling and tensile strength and compression is established. In the future, the material obtained by this technology can be used in landscape design.Â Â